Range extension of Lesser Three-ring Ypthima inica Hewitson (1864) (Lepidoptera: Nymphalidae) southwards to the Northern Western Ghats, India - Sawant, Mandar Anil (Journal of the Bombay Natural History Society (JBNHS), 2015)
No Abstract.